The moderating role of partner support among smokers and abstainers - Maria da Graça Pereira (Universidade de Fortaleza, 2014)
Objective: To analyze the moderating effect of partner support in the relationship between psychological morbidity and quality of life among smokers and abstainers. Methods: This observational cross-sectional study assessed "partner support", "psychological morbidity" (depression, anxiety and stress) and "quality of life" in a convenience sample of 224 smokers and 169 abstainers through questionnaires that were validated and analyzed using regression and simple slopes. Results: Partner support (positive and negative) among smokers appeared as a moderator in the relationship between psychological morbidity and physical quality of life. As for mental quality of life, the partner support did not have a moderating effect. The results among abstainers are similar to those found among smokers. When positive partner support is strong, there is an opposite relationship between psychological morbidity and quality of life. However, this relationship is stronger when negative partner support is strong and, in this case, the relationship between psychological morbidity and quality of life is negative. Conclusion: Partner support, whether positive or negative, was an important moderator concerning quality of life and psychological morbidity of smokers and abstainers. doi:10.5020/18061230.2013.p349